Effectiveness Of Cooperative Learning Model In Economics Subject On Student Engagement Of High School Students In Tegal Regency - Puspasari, Elsa; Nasori, Ahmad; Aslindar, Dwi Astarni; Hidayati, Umi (Soedirman Economics Education Journal, 2023)
Improving the quality of human life of a country is needed in an era of civilisation that continues to experience changes from all aspects, especially technology and information. The ability that students have is inseparable from the learning process carried out at school by involving teachers, students, learning resources and learning facilities. This study aims to find the effectiveness of cooperative learning models in Economics subjects on student engagement. The experimental method with a quasi-experimental approach was used to find out the results of the study. sampling technique using Cluster Random Sampling. In this study, the population was 78 class X students and the research subjects used 52 students for the control class and the experimental class. Hypothesis testing using independent sample t-test. The results showed that the cooperative learning model in economic subjects was effective and significantly affected student engagement in class X students of SMA NU Hasyim Asy'ari Tegal with a t-table value of 3.964 with a sig value. 0,003<0,05.